Prefaces to Canon Law books in Latin Christianity : selected translations, 500-1317 - Somerville, Robert, 1940-; Brasington, Bruce C., 1957- (Studies in medieval and early modern canon law ;, 2020)
"Through their translations, with commentaries, of prefaces to medieval canonical collections, the authors trace the development of medieval ecclesiastical law. The first edition of this book was published by Yale University Press in 1998. This second edition includes additional translations, expanding the scope of the study by nearly a century, to 1317; and also a bibliographical essay discussing new scholarship in the field since the first edition"--